On the taxonomic placement of the Cuban spider Nops ariguanabo Alayón and the description of a new Mexican Tarsonops (Araneae, Caponiidae) - Ruiz, Alexander Sánchez; Brescovit, Antonio D. (Zootaxa, 2015)
The Cuban spider species Nops ariguanabo Alayón, 1986 is transferred to the genus Tarsonops Chamberlin based on the presence of several false sutures on the anterior tarsi and metatarsi, and a broad, subcircular carapace. A redescription of the species, including the description of female internal genitalia is provided. Additionally, a new species of Tarsonops from Mexico is described. The first SEM photos and a new diagnosis for the genus Tarsonops are included.